Morphology and growth among mutant turfgrass cultivars under different rates of nitrogen - Sabri, Nurnabilah (2015)
An experiment was conducted at Turf Unit, Taman Pertanian Universiti, UPM to study the morphology and growth among mutant turfgrass cultivars under different rates of nitrogen. Five cultivars of each mutant Cowgrass (Axonopuss compressus) and Hybrid Bermudagrass (Cynodon dactylon) were used as planting materials. Urea fertilizer was applied as the source of nitrogen at different rates 0, 0.15, 0.30, and 0.45kg/100m2/month for Cowgrass, and 0, 0.25, 0.50, 0.75kg/100m2/month for Bermudagrass. The fertilizer was applied every two weeks in both species. The experiment was arranged in Randomized Complete Block Design (RCBD) with two factorials and four replications. Urea fertilizer was applied to three months old mutant cultivars for 28 weeks in the early morning. Growth and morphological data visual (ligule, auricle, vernation, leaf blade and sheath, and collar), growth rate of coverage (m2), leaf characteristics (length and width) (cm), plant density, root volume (cm3), shoot and root dry weight (g), and ratio of dry weight of root to shoot were recorded. The result revealed that there were significant differences among the cultivars in each species based on the different rate of fertilizer application. For Axonopus compressus, the treatment of nitrogen application of 0.489 gram (T3) gave the best effect on growth of mutant Axonopus compressus cv A13, Axonopus compressus cv A23, Axonopus compressus cv A26 - 2, Axonopus compressus cv A48, and original of Axonopus compressus (control). The best cultivar for this species was Axonopus compressus cv A23 and Axonopus compressus cv A48. For Hybrid Cynodon dactylon, the treatment of nitrogen application of 0.815 gram (T3) gave the best effect in growth of mutant Cynodon dactylon cv Satiri, mutant Cynodon dactylon cv TifEagle, Cynodon dactylon cv Tifdward, Cynodon dactylon cv TifEagle, and Cynodon dactylon cv Satiri (control). The best cultivar for this hybrid species was hybrid Cynodon dactylon cv Satiri (control). The experiment needs to be repeated to confirm these results.